Life expectancy in Germany based on the 2011 census: Was the healthy migrant effect merely an artefact? - Nieden, Felix zur; Sommer, Bettina (Bundesinstitut für Bevölkerungsforschung, 2016)
The Federal Statistical Office's 2010/12 general life table is the first to provide results on life expectancy based on census data for reunified Germany. This article therefore examines the question of how the revisions of the population figures from the 2011 census affected the measured life expectancy. To do so, we analysed both the official life tables based on the old intercensal population updates before the census and those based on the population data from the 2011 census. The method used to calculate the census-adjusted 2010/12 general life table was also transferred to separate life tables drawn up for the German and the foreign population. In this way, findings on the so-called "healthy migrant effect" can be discussed, ruling out possible errors in the intercensal population updates. These errors had previously been cited as the main causes for a distinctly longer life expectancy among the foreign population compared with the German population. As expected, a census-based calculation for the total population and for the German population resulted in only minor revisions to the life expectancy figures. The use of the census results does, however, distinctly alter the life expectancy of foreign women and men. An advantage of over 5 years in life expectancy at birth, measured on the basis of the old population data, needs to be revised to about 2.9 years for men and 2.1 years for women based on the 2011 census. The healthy migrant effect therefore cannot be traced back solely to data artefacts from the old intercensal population updates - even with revised data, the foreign population shows marked survival advantages.
Keywords: Bevölkerungsentwicklung; Bevölkerungsprognose; Einwanderung; Demographischer Wandel; Lebenserwartung; Migrant; Inländer; Zuwanderung; Einflussfaktor; Migrant; Gesundheitszustand